STUDI KELAYAKAN BISNIS USAHA SABLON DI UD. ANANTA DESA ADAT KAPAL KECAMATAN MENGWI KABUPATEN BADUNG - Ni Luh Ketut Ayu Sudha Sucandrawati; Ni Wayan Ari Sudiartini (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2022)
: The screen printing business is a business engaged in printing services both from batik uniform printing to school uniforms, in this study which aims to analyze the business feasibility study to improve the screen printing business UD. Ananta in the Desa Adat Kapal, Mengwi District, Badung Regency, viewed from several aspects of both marketing aspects, legal aspects, technical and technological aspects, environmental aspects, financial and financial aspects, this study uses descriptive qualitative research with interview methods. The results obtained from this study indicate that company management consists of Planning, Organizing, Actuating, Controlling. However, there are problems that occur in the external environment showing the level of competition both from the threat of changing school batik uniforms to school endek. Therefore the strategy used for the development of the screen printing business is to improve the quality of production which will affect the results given to consumers. From the financial aspect, the NPV (Net Present Value) value is Rp. 208,575,502, IRR (Internal Rate of Return) 13.49%, PI (Profitability Index) 1.6. NPV is said to be feasible because it has a positive value, an IRR that is declared feasible because the interest rate on the net cash flow of a project is positive and the PI is feasible because it has more than one value so that the company is feasible to realize.